A new revolution in Malays' names: The association of identity identification with English language learning perception - Amin N.M.; Abdul Rahman N.A. (Taylor and Francis - Balkema, 2023)
A way of living that is based on values, customs, norms, and religion often forms one's racial as well as national characteristics. Nevertheless, names being an important identity marker for Malays in Malaysia as Muslims, seem to be loosely related to representing their religious identity today. This is because their identity as Muslims is ironically manifested in their English-resembled names (à la English names) instead of Arabic names, which clearly indicates their disregard for Islamic teachings. However, looking on the positive side, the à la English names of the Malays can perhaps play a major role in motivating them to improve and master their English. In essence, the study examines whether the Malays' perception towards their à la English names as part of their identity could motivate them to learn English. The results revealed that there was a correlation between these two variables of the study. © 2014 Taylor & Francis Group.